2015
DOI: 10.1016/j.eurpsy.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of functional capacity and real-world functioning in patients with schizophrenia

Abstract: In patients with schizophrenia, functional capacity and real-world functioning are two related but different constructs. Each one predicts the other along with other factors; general psychopathology for functional capacity, and severity of the illness and negative symptoms for real-world functioning. These findings have important clinical implications: (1) both types of functioning should be assessed in patients with schizophrenia and (2) strategies for improving them should be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 37 publications
6
24
0
4
Order By: Relevance
“…Schizophrenia is associated with substantial impairments in functional outcomes, including social and occupational functioning, independent living, and the ability to perform activities of daily living ( Green, Kern, Braft, & Mints, 2000 ). Additionally, several studies have shown that cognitive functions are impaired in patients with schizophrenia, and these impairments also have a real impact on the daily functioning of patients with this disorder ( García-Portilla et al, 2014 , Gavilán and García-Albea, 2014 , Menéndez-Miranda et al, 2015 ). They include significant deficits in memory, attention, problem solving, processing speed, and social cognition, which have been shown to be associated with several of the aforementioned functional impairments ( Keefe et al, 2013 ).…”
mentioning
confidence: 99%
“…Schizophrenia is associated with substantial impairments in functional outcomes, including social and occupational functioning, independent living, and the ability to perform activities of daily living ( Green, Kern, Braft, & Mints, 2000 ). Additionally, several studies have shown that cognitive functions are impaired in patients with schizophrenia, and these impairments also have a real impact on the daily functioning of patients with this disorder ( García-Portilla et al, 2014 , Gavilán and García-Albea, 2014 , Menéndez-Miranda et al, 2015 ). They include significant deficits in memory, attention, problem solving, processing speed, and social cognition, which have been shown to be associated with several of the aforementioned functional impairments ( Keefe et al, 2013 ).…”
mentioning
confidence: 99%
“…13 Positive symptoms can affect specific areas, such as self-care and aggressive behavior, but tend to be clinically relived through antipsychotic treatment. 35 Thus, it is interesting to see whether blood cytokine levels in early stage of SCz can predict the final therapeutic effect of these symptoms and whether they can reduce negative and depressive symptoms that may lead to a reduction in the level of disability. Our research showed that higher IL-6 levels predict a reduced improvement in depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery obviously depends on remission. Nevertheless, there are a number of other intervening factors affecting recovery that are responsible for the marked variation in outcome observed (Menendez-Miranda et al, 2015;Jordan et al, 2014).…”
Section: Introductionmentioning
confidence: 98%